An investigation of a solar cooker with parabolic trough concentrator. (September 2019) - Noman, Muhammad; Wasim, Ahmad; Ali, Muzaffar; Jahanzaib, Mirza; Hussain, Salman; Ali, Hafiz Muhammad Khurram; Ali, Hafiz Muhammad
Abstract: This research aims to develop a simple mathematical model for performance evaluation of a thermally exposed solar parabolic trough cooker. It was done under open environmental climate conditions for domestic uses. The experimental setup consisted of a solar cooker made of polished parabolic trough stainless steel having concentration ratio 9.867. The efficiency analysis depicts that the resulted parabolic trough optical efficiency range between 53-33%, theoretical efficiency between 50-30% and the experimental efficiency between 38-5%. Additionally, the maximum water temperature achieved was 37.2 °C at the outlet of parabolic trough. However, maximum water temperature achieved by parabolic trough cooker was 53.6 °C under stagnated conditions. Furthermore, the observed cooker energy efficiency range between 6.5-0.11% and exergy efficiency was in range between 7.6 × 10 −2 - 2.1 × 10 −2 % for direct cooking. Results found helpful for making domestic useable cooker.